Changes in use of emergency contraceptive pills in the United States from 2008 to 2015 - Rubina Hussain; Megan L. Kavanaugh (Elsevier, 2021)
Objectives: To describe changes in use and receipt of emergency contraceptive (EC) pills among women in the United States during a period of key EC policy changes, from 2008 to 2015. Study design: Using data from the 2006 to 2010 and 2013 to 2017 National Surveys of Family Growth, we present changes in the percent of women who ever used EC between 2008 and 2015 by select sociodemographic and sexual and reproductive health characteristics, and we examine multivariable relationships of these characteristics with EC ever use in 2015. We also examine changes in repeat EC use, receipt of EC counseling, reasons for EC use and source of EC between the time periods. Results: Among sexually experienced women ages 15 to 44, EC ever use increased from 11% in 2008 to 23% in 2015 overall and among nearly all groups of women. In 2015, age 20 to 29, non-Hispanic other or Hispanic race, at least a high school education, working part-time, income at least 100% of the federal poverty level, ever having been married, and having received EC counseling in the prior year all represent characteristics associated with higher odds of having ever used EC. In 2015, a smaller share of women last obtained EC with a prescription or at a health facility than in 2008. Conclusions: Increases in EC use occurred as access to EC was broadened through regulatory changes that moved some forms of EC from behind-the-counter to fully over-the-counter between 2008 and 2015. Implications: Over-the-counter provision of many forms of EC pills may have increased access and introduced more flexibility in how EC is obtained, but these changes may have come with tradeoffs, both in the form of cost barriers and decreased opportunities for clinicians to discuss EC with their patients. Despite improved access to contraception more broadly through the Affordable Care Act, EC remains a necessary component of the overall contraceptive method mix, and clinicians can play a key role in discussing EC as one option among many during contraceptive counseling sessions.